Islamic Republic of Iran : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that with high oil prices and a significant policy stimulus, the Iranian economy continued to grow strongly in 2005-06. Real GDP growth is estimated at 5 1\2 percent. Oil GDP growth was modest owing to capacity constraints, while non-oil GDP growth was broad based, reaching 6 percent. The tensions associated with the nuclear issue, however, had some adverse effects on private investment. With energy prices projected to remain high and external demand continuing to support non-oil exports, Iran's near-term growth prospects look favorable.